Investigating Self Professional Development in Teaching English: The Case of English College Teachers’ Role as Models - Nurhayati, Dwi Astuti Wahyu (Dinamika Ilmu: Jurnal Pendidikan, 2018)
Self Professional Development is one of the key factors in Foreign Language Learning, and therefore strategies in developing English professional college teachers should be seen as an important aspect of improving English lecturers’ role as models. This study was done through a survey to 30 EFL college teachers of PGRI Teacher Training College and State Islamic Institute of Tulungagung, a small town in East Java, Indonesia, in order to underline the basis of making a decision on improving efforts for the sake of creating English Professional Development college teachers who are influential toward the success of English teaching and learning process. The instrument -a questionnaire including three open ended questions-was developed in accordance to reviewing some related research articles about professional developing. This study reveals the fact that to be a professional English college teachers, one should develop ten professional efforts namely perceived professional identity as model; career development needs, theoretical and content knowledge; practical knowledge and professional skills; professional networking; pedagogical content knowledge; perceived benefits of ICT use to students (perceived by the teacher); perceived benefits to the college teachers (self); engaging conducting research.